Physical developement of children from Lublin in the age 0-17 years - Chrząstek-Spruch, Hanna; Szajner-Milart, Irena (Anthropological Review, 1974)
The authors have made a detailed analysis of anthropometrical measurements (slalure, weight and chest circumterence) ot 10 890 children aged 0-17 years from Lublin. For children with age below 3 years the authors also measured head circumference. Working with the index of development rythm and the index of sexual dymorphism, the authors have analysed growth and sexual differentiation of investigated traits in various age groups.